Enhancing team resilience through team knowledge dynamics: a mediated approach - Yang, Hong; Suntrayuth, Sid (Frontiers in Psychology, 2025)
In rapidly changing and knowledge-driven environments, building resilient teams has become a strategic imperative for knowledge-based organizations, particularly higher education institutions. This paper conceptualizes team dynamic capabilities using the SECI model and examines the serial mediating roles of communicative, leadership, interpretation, and analytical. Using survey data from 617 faculty and staff members in Chinese higher education institutions. The study applies structural equation modeling (SEM) to test the proposed relationships. The results show that these four behavioral capacities serve as partial mediators between team dynamic capability and team resilience, highlighting the importance of knowledge-based team processes in shaping resilience. The findings provide practical implications for higher education institutions in building resilient teams under changing environments.